2020
DOI: 10.3390/ijms21041398
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Non Coding RNA in LIQUID Biopsies as a Promising Biomarker for Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most common cancers worldwide, with a high mortality rate, especially in those that are diagnosed in late stages of the disease. The current screening blood-based markers, such as carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9), have low sensitivity and specificity. Meanwhile, other modalities are either expensive or invasive. Therefore, recent research has shifted towards a minimally invasive test, namely, liquid biopsy. Exosomes are favorable molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 140 publications
0
67
0
Order By: Relevance
“…LncRNA expression has been shown to discriminate between tumor and normal tissue better than protein-coding genes [ 13 ]. In this setting, lncRNAs have gained interest as novel biomarkers for CRC determined in both tumor tissue and liquid biopsy samples [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA expression has been shown to discriminate between tumor and normal tissue better than protein-coding genes [ 13 ]. In this setting, lncRNAs have gained interest as novel biomarkers for CRC determined in both tumor tissue and liquid biopsy samples [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that, besides ctDNA and CTC, circulating non-coding RNAs are emerging as important biomarkers for the clinical management of CRC patients ( Rapado-González et al, 2019 ; Baassiri et al, 2020 ). In body fluids, circulating non-coding RNA mainly exist in either the cell-free state or the exosomal form.…”
Section: Methods Of Liquid Biopsymentioning
confidence: 99%
“…Exosomes are relatively more stable than serum at room temperature. These aspects may suggest exosomal circRNAs good diagnostic and prognostic biomarkers ( 158 ).…”
Section: Roles Of Circrnas In Human Cancermentioning
confidence: 99%